CORRELATION AMONG SLEEP DURATION, BLOOD PRESSURE, AND BLOOD GLUCOSE LEVEL OF MORANGAN PEOPLE, SINDUMARTANI, NGEMPLAK, SLEMAN - Gregorius Bhaskara Wikanendra; Rita Suhadi; Christianus Heru Setiawan; Dita Maria Virginia; Phebe Hendra; Fenty Fenty (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2020)
Sleep deprivation is a risk factor for cardiovascular and metabolic diseases. There was a high prevalence of high blood pressure and type 2 diabetes in Morangan, Yogyakarta Province. This study aims at studying the correlation between sleep duration, systolic blood pressure and fasting blood glucose levels of people in Morangan. This study was a cross-sectional study conducted in cooperation with a public health care program for people in Morangan. Data collection was done using a questionnaire and health screening procedure during the public health care program. Collected data were covering aspects of systolic blood pressure, fasting blood glucose, sleep duration, and sleep habit. There was a high prevalence of high systolic blood pressure (130mmHg; 66.04%) and high fasting blood glucose level (100mg/dL; 39.62%) in Morangan people. There was a significantly positive correlation between sleep duration and systolic blood pressure (p:0.024; r:0.31) but no significant correlation between sleep duration and fasting blood glucose level. The major contributing habits towards sleep deprivation were caffeine consumption and medium pre-sleep routine. The result of this research will provide help in designing an education program for people of Morangan in preventing and treating high blood pressure and type 2 diabetes.